Baseline for assessing the impact of fairtrade certification on cocoa farmers and cooperatives in Côte d’Ivoire - Foundjem-Tita, D.; Degrande, A.; Donovan, J.; Stoian, D.; Kouamé, C. (World Agroforestry Centre, 2017)
In 2014, Fairtrade International, Fairtrade Africa, the World Agroforestry Centre (ICRAF) and Bioversity International initiated a collaboration for the development of a multidimensional baseline on small-scale cocoa farmers and their cooperatives in West Africa. The baseline is expected to provide a fuller understanding of the current situation for Fairtrade cocoa production and marketing as well as provide the foundation for rigorous assessment of outcomes and impacts of Fairtrade certification on cocoa cooperatives and smallholder households in West Africa in the future. Côte d’Ivoire and Ghana, the two largest Fairtrade cocoa producers in West Africa, provide about 68 percent of the cocoa that is sold under Fairtrade terms in global markets. In 2013, the year this study was commissioned, the volume of Fairtrade cocoa sold from West Africa reached 133 400 tonnes, involving 71 cooperatives and producer associations and 138 800 farmers. Most of this cocoa originated from Côte d’Ivoire and Ghana. The rapid growth in the number of cocoa-producing organizations joining the Fairtrade system in Côte d’Ivoire and Ghana provides a unique opportunity to build a baseline on Fairtrade cocoa producers in West Africa for future monitoring and impact assessment. This report focuses on the Fairtrade cocoa baseline for Côte d’Ivoire (a similar report is available for Ghana). It describes the conceptual framework and methods used in the design of the baseline, followed by an assessment of the context in Côte d’Ivoire. Key features of the baseline data at the cooperative and household levels are covered in detail. The report concludes with some recommendations to Fairtrade for expanding Fairtrade International in Côte d’Ivoire and for follow-up actions for future baseline work.